Formulation and Evaluation of Nanoemulsions Combination of Black Cumin Seed Oil (Nigella sativa L.) and Moringa Seed Oil (Moringa oleifera L.) as Sunscreen - Dessy Erliani Mugita Sari; Della Triyana Puryanti; Ricka Islamiyati; Luvita Gabriel Zulkarya; Bagus Riyanto (LPPM Akafarma Sunan Giri Ponorogo, 2025)
Nanoemulsion preparations can improve quality and facilitate the penetration of active ingredients into the skin. Black cumin seed oil (Nigella sativa L.) and Moringa seed oil (Moringa oleifera L.) contain flavonoids that can absorb UV rays. This study aims to determine the physical properties and SPF value of nanoemulsion preparations as a sunscreen combination of black cumin seed oil and moringa seed oil. Nanoemulsion preparations with variations in the concentration of black cumin seed oil: moringa seed oil at F1 4:0, F2 0:4, F3 2:2, F4 3:1 and F5 1:3. Nanoemulsion preparations are evaluated for their physical and chemical properties such as organoleptis test, pH, viscosity, percent transmittance, particle determination test and SPF value. The results showed that variations in the concentration of black cumin seed oil and moringa seed oil affected to the test except in viscosity, statistical tests on pH tests and SPF tests have significant differences. The results of the transmittance percent test, perticle size test and polydispersity index of the preparation are in the ideal range. The potential zeta test results of the preparation do not fall within the ideal range. Black cumin seed oil and moringa seed oil in nanoemulsion preparations meet the parameters of good physical properties, organoleptis test, pH test, viscosity test, transmittance percent test, , while in particle determination test it does not meet the requirements on potential zeta measurement. Formula 1 is the optimal formula of nanoemulsion preparations as sunscreens.